Biological Utilization Of Fibre In Swine Under Various Nutrient Regimes - Ong, Hwee Keng (1984)
Five experimcnts mark conducted to study the biological utilization of fibre in growing;-finishinq piqs under various nutrient regime. Two fibrous feedstuffs viz China leaf meal'(CLM) and ' brewers dried grains (BDG) were used as the main fibre sources. In Experiment 1, the chemical ccmposition, fibre Clnd bulk characteristics of CLM ,mel BDG were elucidated. Sample were analyzed For dry matlet (DM) Crude protein (CI),ther extract (EE),crude fibre (ADF),acid detergent lignin (ADL),cellulose, hemicellulose ,calcium, phosphorus and amino acid. Characterization of the wet and dry bulk of CLM ,and BDG in terms of weight per uni t volume, increased wet volume on soaking and relative dry volume showed that BDG had a higher bulk than did CLM. If qround maize were incexed at 100% for weiqht per unit volume, CLM and BDG showed an equivalent relative weight of 44.8 and 27.8%, respectively.